Anti-adhesion liquid packaging film and preparation process thereof
By using PE-SILICON-PE block copolymer and nanosilicon dioxide composite in the packaging film, the adhesion problem of non-Newtonian liquid food products is solved, and an efficient anti-adhesion effect is achieved and food waste is reduced.
Patent Information
- Application Number
- CN202510090850.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Non-Newtonian liquid food products such as milk, yogurt and juice are prone to stick to plastic packaging film, resulting in food waste and resource waste.
An anti-adhesion liquid packaging film was developed to improve the anti-adhesion properties of the packaging film by using the surface modifier PE-SILICON-PE block copolymer and the hydrophobic modifier nanosilica composite.
The prepared anti-adhesive liquid packaging film not only has excellent anti-adhesive properties, but will not be contaminated when packaging. It is suitable for packaging liquid products such as sauces and yogurt. It will have a non-stick effect after packaging, making it convenient for consumers to use.
Smart Images

Figure CN119820963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research and development of anti-adhesion packaging materials, and in particular to an anti-adhesion liquid packaging film and a preparation process thereof. Background Art
[0002] Non-Newtonian liquid food products such as milk, yogurt, honey and juice have high viscosity and complex fluidity, and are easily adhered to the surface of plastic packaging film, making it difficult to squeeze out during use, resulting in serious food and resource waste. Therefore, the development of easy-to-extrude anti-sticking packaging materials has practical industrial application value.
[0003] At present, the common product structures of plastic packaging films on the market are: PET / PA / PE, PET / Al / PA / PE, PA / PE, PET / VMPET / EVAPE, PET / Al / EVAPE, PA-TIE-PE-PE-TIE-PA-TIE-PE-PE, PE / PE-g-MAH / EVOH / PE-g-MAH / PE. By modifying the constituent materials of these structures, such as adding hydrophobic substances, the hydrophobic properties of plastic packaging films can be significantly improved. For example, the Chinese patent with the authorization number CN118024637B discloses a preparation process and application of a modified polypropylene packaging sheet, which significantly improves the anti-sticking properties of the polypropylene sheet by modifying the polypropylene resin raw material with silicone oil and silicon dioxide nanoparticles.
[0004] The study found that the surface modifier PE-SILICON-PE block copolymer composed of polyethylene and silicon can be used to improve the anti-adhesion properties of polyethylene films. Summary of the invention
[0005] The present invention develops a novel anti-adhesion component, which is composited by a surface modifier PE-SILICON-PE block copolymer and a hydrophobic modifier nano-silica. The anti-adhesion component is used to improve the anti-adhesion performance of a packaging film. The prepared liquid packaging film has not only excellent anti-adhesion performance, but also a sealing portion that will not be contaminated during packaging. The film is very suitable for packaging liquid products such as sauces (fruit sauce, sesame paste), yogurt, etc., and has a non-stick effect after packaging, which is convenient for consumers to use.
[0006] A preparation process of an anti-adhesion liquid packaging film comprises the following steps:
[0007] Step 1: Using cyclohexyltrimethoxysilane as a raw material, a hydrolysis-condensation method and a vertex-capping method are used to prepare an octacyclohexyl double-layer cyclic siloxane monomer containing a Si-H bond;
[0008] Step 2: preparing an organic-inorganic hybrid linker by reacting the Si-H bond of the octacyclohexyl double-layer cyclic siloxane monomer with the alkenyl functional group of the allyl silane coupling agent;
[0009] Step 3: The Si-OH functional group obtained by the hydrolysis reaction of the hydrolysis functional group of the organic-inorganic hybrid linker undergoes a dehydration condensation reaction with the -OH functional group on the surface of the hydroxylated silica nanoparticle, thereby modifying the organic-inorganic hybrid linker on the surface of the silica nanoparticle to obtain modified silica nanoparticles;
[0010] Step 4: dispersing the modified silica nanoparticles in the PE-SILICON-PE block copolymer matrix to prepare an anti-adhesion composite material;
[0011] Step 5: Setting a nine-layer co-extruded film structure, introducing the anti-adhesion composite material into the first layer and the ninth layer of the nine-layer co-extruded film, and adopting a nine-layer co-extrusion blow molding film forming process to prepare an anti-adhesion liquid packaging film.
[0012] Preferably, the allylsilane coupling agent is one of allyltrichlorosilane, allyltrimethoxysilane and allyltriethoxysilane.
[0013] Preferably, the preparation method of the octacyclohexyl double-layer cyclic siloxane monomer is:
[0014] Step S3-1: using cyclohexyltrimethoxysilane as a raw material, adopting a hydrolysis-condensation method, catalyzing the hydrolysis and polycondensation reaction of cyclohexyltrimethoxysilane with sodium hydroxide to generate octacyclohexyltetrasilanol sodium salt;
[0015] Step S3-2: using octacyclohexyltetrasilanol sodium salt as a raw material and methyldichlorosilane as a capping agent, an octacyclohexyl double-layer cyclic siloxane monomer is synthesized by a vertex-capping method under the catalysis of triethylamine.
[0016] Preferably, the formula and dosage of each film layer of the anti-adhesion liquid packaging film are as follows:
[0017] First layer: the formula is 40-80wt% low-density polyethylene resin and 20-60wt% anti-adhesion composite material, the amount is 10-30 parts by weight;
[0018] The second layer: the formula is 100wt% high-density polyethylene resin, the amount is 5-15 parts by weight;
[0019] The third layer: the formula is 100wt% low-density polyethylene resin, the amount is 5-15 parts by weight;
[0020] The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight;
[0021] The fifth layer: the formula is 100wt% ethylene-vinyl alcohol copolymer resin, the amount is 5 to 15 parts by weight;
[0022] The sixth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight;
[0023] The seventh layer: the formula is 100wt% low-density polyethylene resin, the amount is 5 to 15 parts by weight;
[0024] The eighth layer: the formula is 100wt% high-density polyethylene resin, the amount is 5 to 15 parts by weight;
[0025] The ninth layer: the formula is 40-80wt% of low-density polyethylene resin and 20-60wt% of anti-adhesion composite material, and the amount is 10-30 parts by weight.
[0026] Preferably, the preparation method of the anti-adhesion liquid packaging film is as follows: each layer of raw materials is respectively put into the hopper of nine screw extruders of a nine-layer co-extrusion film blowing unit, after stirring and mixing, the molten resin is converged at the head of the die through a diverter, and is extruded and blown through a die head, the blow-up ratio is controlled at 2.5 to 2.9, cooled, and rolled up to obtain an anti-adhesion liquid packaging film with a thickness of 50 to 150 μm;
[0027] Preferably, the formula of the anti-adhesion composite material is that the mass ratio of hydroxylated silica nanoparticles, organic-inorganic hybrid linker, and PE-SILICON-PE block copolymer is (0.5-5):1:(3-20).
[0028] Preferably, the particle size of the hydroxylated silica nanoparticles is 40 to 80 nm.
[0029] The anti-adhesion liquid packaging film prepared according to the above process is used in the field of non-Newtonian liquid product packaging.
[0030] Beneficial effects:
[0031] The present invention first prepares a novel anti-adhesion component, which is composed of a surface modifier PE-SILICON-PE block copolymer and a hydrophobic modifier nano-silica, and is compounded using an organic-inorganic hybrid linker with excellent hydrophobic properties; then a nine-layer co-extruded film structure is set, the anti-adhesion component is introduced into the first layer and the ninth layer of the nine-layer co-extruded film, and a nine-layer co-extrusion blow molding film forming process is adopted to prepare an anti-adhesion liquid packaging film;
[0032] The experimental results show that the anti-adhesion liquid packaging film has excellent anti-adhesion properties and can achieve a non-stick effect when used to package non-Newtonian liquid products such as yogurt. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the chemical structural formula of octacyclohexyltetrasilanol sodium salt;
[0034] Figure 2 is the chemical structural formula of octacyclohexyl bicyclic siloxane monomer;
[0035] Figure 3 is the chemical structural formula of an organic-inorganic hybrid linker;
[0036] Wherein, Cy is cyclohexyl;
[0037] Figure 4 Performance test results of anti-adhesion liquid packaging film. DETAILED DESCRIPTION
[0038] The present invention uses silicon dioxide nanoparticles with excellent hydrophobic performance and PE-SILICON-PE block copolymer as anti-adhesion modification raw materials. In order to improve the compatibility of silicon dioxide nanoparticles and PE-SILICON-PE block copolymer, a linker containing octacyclohexyl double-layer cyclic siloxane with hydrophobic ability is developed. Hydroxylated silicon dioxide nanoparticles are first modified by using the new linker, and then compounded with PE-SILICON-PE block copolymer to obtain an anti-adhesion composite material.
[0039] Experimental Example 1:
[0040] The preparation process of the octacyclohexyl double-layer cyclic siloxane monomer is as follows:
[0041] (1) Synthesizing sodium octacyclohexyltetrasilane, wherein the synthesis method is as follows: using cyclohexyltrimethoxysilane as a raw material, adopting a hydrolysis-condensation method, catalyzing the hydrolysis and polycondensation reaction of cyclohexyltrimethoxysilane with sodium hydroxide to generate sodium octacyclohexyltetrasilane, wherein the chemical structure is as follows: Figure 1 As shown, the specific experimental steps are as follows: under the protection of nitrogen, 20.4g of cyclohexyltrimethoxysilane, 2.7g of sodium hydroxide, 100mL of isopropanol and 5mL of deionized water are added to a three-necked flask, the temperature is raised to 40°C and stirred until all dissolved, the temperature is further raised to 90°C and stirred and refluxed for 4h, the temperature is cooled to room temperature and stirred for 15h, filtered, repeatedly washed with isopropanol, and vacuum dried to obtain octacyclohexyltetrasilanol sodium salt;
[0042] (2) Synthesizing an octacyclohexyl double-layer cyclic siloxane monomer, wherein the synthesis method is as follows: using octacyclohexyl tetrasilanol sodium salt as a raw material, using methyldichlorosilane as a capping agent, and synthesizing the octacyclohexyl double-layer cyclic siloxane monomer by a top angle-capping method under the catalysis of triethylamine. The chemical structure is as follows Figure 2As shown, the specific experimental steps are as follows: under the protection of nitrogen, 6.0 g of octacyclohexyltetrasilanol sodium salt, 1.5 mL of triethylamine and 50 mL of tetrahydrofuran are added to a three-necked flask, placed in an ice bath and stirred for dissolution for 2 h, then 10 mL of a tetrahydrofuran solution containing 1.5 g of methyldichlorosilane is slowly added dropwise to the three-necked flask, the ice bath is removed, the reaction is stirred at room temperature for 24 h, the solvent is removed by rotary evaporation, the mixture is repeatedly washed with methanol, and vacuum dried to obtain an octacyclohexyl double-layer cyclic siloxane monomer;
[0043] The nuclear magnetic resonance hydrogen spectrum of the octacyclohexyl bilayer cyclic siloxane monomer is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.09 (s, 6H), 1.48-1.69 (m, 88H), 3.53 (s, 2H).
[0044] Experimental Example 2:
[0045] An organic-inorganic hybrid linker is prepared by reacting the Si-H bond of an octacyclohexyl double-layer cyclic siloxane monomer with the alkenyl functional group of an allyl silane coupling agent to generate an organic-inorganic hybrid linker having a chemical structure as shown in Figure 3 As shown;
[0046] The allyl silane coupling agent is one of allyl trichlorosilane, allyl trimethoxysilane and allyl triethoxysilane; in this experimental example, allyl trichlorosilane is selected;
[0047] The specific experimental steps of the organic-inorganic hybrid linker are as follows: under the protection of nitrogen, 3.0 g of octacyclohexyl double-layer cyclic siloxane monomer and 30 mL of anhydrous toluene are added to a three-necked flask, stirred at room temperature until completely dissolved, and then 10 mL of allyl trichlorosilane solution (prepared by 1.0 g of allyl trichlorosilane amine and 10 mL of anhydrous toluene) and 4 drops of Custer catalyst are sequentially added to the three-necked flask, the temperature is raised to 80° C. and stirred for reaction for 24 h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain an organic-inorganic hybrid linker;
[0048] The H NMR spectrum of the organic-inorganic hybrid linker is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.55 (s, 6H), 0.97-1.13 (m, 4H), 1.48-1.69 (m, 88H), 1.78-1.82 (t, 4H), 2.08-2.15 (m, 4H).
[0049] Embodiment 1:
[0050] (1) preparing modified silica nanoparticles, wherein the preparation method comprises: performing a dehydration condensation reaction between the Si-OH functional group obtained by the hydrolysis reaction of the silicon chlorine group of the organic-inorganic hybrid linker and the -OH functional group on the surface of the hydroxylated silica nanoparticle, and modifying the organic-inorganic hybrid linker on the surface of the silica nanoparticle to obtain the modified silica nanoparticles, wherein the specific experimental steps are: adding 3 g of hydroxylated nano-silica powder, 40 mL of ethanol and 10 mL of deionized water into a four-necked bottle, stirring and reacting in a 40° C. water bath for 1 h, then adding 2 g of the organic-inorganic hybrid linker into the four-necked bottle, heating to 60° C. and stirring and reacting for 3 h, cooling to room temperature and standing for 10 h, filtering by suction, washing with deionized water, centrifuging, and vacuum drying to obtain the modified silica nanoparticles;
[0051] An anti-adhesion composite material is prepared, and the preparation method thereof is as follows: modified silicon dioxide nanoparticles are dispersed in a PE-SILICON-PE block copolymer matrix to prepare the anti-adhesion composite material, and the specific experimental steps are as follows: 30 g of PE-SILICON-PE block copolymer and 5 g of modified silicon dioxide nanoparticles are added into a twin-screw extruder, and the anti-adhesion composite material is prepared by blending, melting, extruding and pelletizing through the twin-screw extruder;
[0052] The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-3 are 130°C, 150°C, and 175°C, respectively, and the rotation speed is 40 r / min.
[0053] (2) preparing an anti-adhesion blend material, wherein the preparation method is: directly dispersing silica nanoparticles in a PE-SILICON-PE block copolymer matrix to prepare an anti-adhesion blend material, wherein the specific experimental steps are the same as those of the preparation experiment of the anti-adhesion composite material, and the only difference is that the modified silica nanoparticles are replaced by hydroxylated nano-silica powder;
[0054] Among them, PE-SILICON-PE block copolymer was purchased from Shanghai Yiqing Trading Co., Ltd., and its model is EXFOLA-PE3027; hydroxylated nano-silica powder was purchased from Beijing Zhongke Keyou Technology Co., Ltd., and its particle size is 40-80 nm.
[0055] Embodiment 2:
[0056] (1) Preparing an anti-adhesion liquid packaging film comprises the following steps:
[0057] Step 1: Set the anti-adhesion liquid packaging film to a nine-layer symmetrical film structure, and the formula and dosage of each film layer are as follows:
[0058] First layer: the formula is 60wt% low-density polyethylene resin and 40wt% anti-adhesion composite material, the amount is 20 parts by weight;
[0059] The second layer: the formula is 100wt% high-density polyethylene resin, the amount is 10 parts by weight;
[0060] The third layer: the formula is 100wt% low-density polyethylene resin, the amount is 10 parts by weight;
[0061] The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 5 parts by weight;
[0062] The fifth layer: the formula is 100wt% ethylene-vinyl alcohol copolymer resin, the amount is 10 parts by weight;
[0063] The sixth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 5 parts by weight;
[0064] The seventh layer: the formula is 100wt% low-density polyethylene resin, the amount is 10 parts by weight;
[0065] The eighth layer: the formula is 100wt% high-density polyethylene resin, the amount is 10 parts by weight;
[0066] Ninth layer: the formula is 60wt% low-density polyethylene resin and 40wt% anti-adhesion composite material, the amount is 20 parts by weight;
[0067] Step 2: Put the raw materials in step 1 into the hoppers of nine screw extruders of a nine-layer co-extrusion film blowing unit respectively, stir and mix, and then the molten resin is converged at the head of the die through a diverter, and then extruded and blown through a die head, and the blow-up ratio is controlled at 2.7, and then cooled and rolled to obtain an anti-adhesion liquid packaging film with a thickness of 60 μm;
[0068] Among them, the process parameters of the screw extruder corresponding to the first, second, third, seventh, eighth and ninth layers are set as follows: the temperature of zones 1-3 is 130°C, 150°C and 175°C respectively, the flow channel temperature is 170°C, and the speed is 30r / min;
[0069] The process parameters of the screw extruder corresponding to the fourth and sixth layers were set as follows: the temperatures of zones 1-3 were 120°C, 140°C, and 165°C, respectively, the flow channel temperature was 160°C, and the rotation speed was 15 r / min;
[0070] The process parameters of the screw extruder corresponding to the fifth layer are set as follows: the temperatures of zones 1-3 are 180°C, 200°C, and 210°C, respectively, the flow channel temperature is 205°C, and the rotation speed is 40 r / min.
[0071] (2) Preparation of packaging film a: Only the anti-adhesion blended material is used to replace the anti-adhesion composite material in the anti-adhesion liquid packaging film, and the rest of the parts are the same as the anti-adhesion liquid packaging film to prepare packaging film a, which is used as comparative example 1.
[0072] (3) Preparation of packaging film b: Referring to the preparation experiment of the anti-adhesion liquid packaging film, the only difference is that no anti-adhesion composite material is used to prepare packaging film b, which is used as comparative example 2.
[0073] Among them, low-density polyethylene resin (LDPE) was purchased from Jiangsu Rantai Plastic Co., Ltd., and its brand is LD 150DW; high-density polyethylene resin (HDPE) was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd., and its brand is FB5600; maleic anhydride grafted polyethylene resin (PE-g-MAH) was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., and its brand is 4288; ethylene-vinyl alcohol copolymer resin (EVOH) was purchased from Guangzhou Best New Material Technology Co., Ltd., and its brand is ET3803RB.
[0074] Performance Test:
[0075] (1) Anti-adhesion performance: The anti-adhesion performance was analyzed by testing the residual amount of yogurt on the sample. The specific test steps were as follows: a 3 cm × 2 cm sample was fixed on a 5 cm × 4 cm long × wide plywood, and a drop of yogurt (Yili original fermented milk) was injected onto the top of the film sample using a 20 mL syringe filled with yogurt. The initial yogurt mass was weighed. To simulate the human body's drinking of yogurt, the test sample was placed at an angle of 45° to the horizontal plane. After the yogurt flowed down, it was left to stand for 20 seconds. The mass of the yogurt remaining after tilting was recorded, and the residual amount of yogurt was calculated. The specific method was as follows:
[0076] Yogurt residue (%) = yogurt mass remaining on the sample after tilting / initial yogurt mass on the sample;
[0077] (2) Barrier properties: The barrier properties of the samples were tested using a Y110 oxygen permeability tester and a TC-03 water vapor permeability tester in accordance with GB / T 1038-2000 and GB / T 1037-2021 respectively;
[0078] (3) Mechanical properties: A 30 mm × 5 mm sample was fixed on an Instron 5565 universal tensile testing machine and subjected to a tensile test at a tensile rate of 5 mm / min. The tensile strengths in the longitudinal and transverse directions were recorded respectively.
[0079] The above experimental results are shown in Table 1 and Figure 4 .
[0080] Table 1 Performance test results of packaging film
[0081]
[0082] Through comprehensive analysis of the above experimental results, the following conclusions can be drawn:
[0083] The anti-adhesion composite material obtained by modifying hydroxylated silica nanoparticles with an organic-inorganic hybrid linker and then compounding them with PE-SILICON-PE block copolymer can significantly reduce the yogurt residue in the packaging film and has a very significant effect on improving the anti-adhesion performance of the packaging film.
Claims
1. A process for preparing an anti-adhesion liquid packaging film, characterized in that: The following steps are involved: Step 1: Using cyclohexyltrimethoxysilane as a raw material, a hydrolysis-condensation method and a vertex-capping method are used to prepare an octacyclohexyl double-layer cyclic siloxane monomer containing a Si-H bond; Step 2: preparing an organic-inorganic hybrid linker by reacting the Si-H bond of the octacyclohexyl double-layer cyclic siloxane monomer with the alkenyl functional group of the allyl silane coupling agent; Step 3: The Si-OH functional group obtained by the hydrolysis reaction of the hydrolysis functional group of the organic-inorganic hybrid linker undergoes a dehydration condensation reaction with the -OH functional group on the surface of the hydroxylated silica nanoparticle, thereby modifying the organic-inorganic hybrid linker on the surface of the silica nanoparticle to obtain modified silica nanoparticles; Step 4: dispersing the modified silica nanoparticles in the PE-SILICON-PE block copolymer matrix to prepare an anti-adhesion composite material; Step 5: Setting a nine-layer co-extruded film structure, introducing the anti-adhesion composite material into the first layer and the ninth layer of the nine-layer co-extruded film, and adopting a nine-layer co-extrusion blow molding film forming process to prepare an anti-adhesion liquid packaging film.
2. The process for preparing an anti-adhesion liquid packaging film according to claim 1, characterized in that: The allylsilane coupling agent is one of allyltrichlorosilane, allyltrimethoxysilane and allyltriethoxysilane.
3. The process for preparing an anti-adhesion liquid packaging film according to claim 1, characterized in that: The preparation method of the octacyclohexyl double-layer cyclic siloxane monomer is: Step S3-1: using cyclohexyltrimethoxysilane as a raw material, adopting a hydrolysis-condensation method, catalyzing the hydrolysis and polycondensation reaction of cyclohexyltrimethoxysilane with sodium hydroxide to generate octacyclohexyltetrasilanol sodium salt; Step S3-2: using octacyclohexyltetrasilanol sodium salt as a raw material and methyldichlorosilane as a capping agent, an octacyclohexyl double-layer cyclic siloxane monomer is synthesized by a vertex-capping method under the catalysis of triethylamine.
4. The process for preparing an anti-adhesion liquid packaging film according to claim 1, characterized in that: The formula and dosage of each film layer of the anti-adhesion liquid packaging film are as follows: First layer: the formula is 40-80wt% low-density polyethylene resin and 20-60wt% anti-adhesion composite material, the amount is 10-30 parts by weight; The second layer: the formula is 100wt% high-density polyethylene resin, the amount is 5-15 parts by weight; The third layer: the formula is 100wt% low-density polyethylene resin, the amount is 5-15 parts by weight; The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight; The fifth layer: the formula is 100wt% ethylene-vinyl alcohol copolymer resin, the amount is 5 to 15 parts by weight; The sixth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight; The seventh layer: the formula is 100wt% low-density polyethylene resin, the amount is 5 to 15 parts by weight; The eighth layer: the formula is 100wt% high-density polyethylene resin, the amount is 5 to 15 parts by weight; The ninth layer: the formula is 40-80wt% of low-density polyethylene resin and 20-60wt% of anti-adhesion composite material, and the amount is 10-30 parts by weight.
5. The process for preparing an anti-adhesion liquid packaging film according to claim 4, characterized in that: The preparation method of the anti-adhesion liquid packaging film is as follows: each layer of raw materials is respectively put into the hoppers of nine screw extruders of a nine-layer co-extrusion film blow molding unit, after stirring and mixing, the molten resin is converged at the head of the machine through a diverter, and is extruded and blow-molded through a die head, the blow-up ratio is controlled at 2.5 to 2.9, and the film is cooled and rolled to obtain an anti-adhesion liquid packaging film with a thickness of 50 to 150 μm.
6. The process for preparing an anti-adhesion liquid packaging film according to claim 1, characterized in that: The formula of the anti-adhesion composite material is that the mass ratio of hydroxylated silicon dioxide nanoparticles, organic-inorganic hybrid connector and PE-SILICON-PE block copolymer is (0.5-5):1:(3-20).
7. The process for preparing an anti-adhesion liquid packaging film according to claim 1, characterized in that: The particle size of the hydroxylated silicon dioxide nanoparticles is 40 to 80 nm.
8. An anti-adhesion liquid packaging film prepared by the process according to any one of claims 1 to 7, characterized in that: The packaging film is used in the field of non-Newtonian liquid product packaging.
Citation Information
Patent Citations
Preparation process and application of modified polypropylene packaging sheet
CN118024637B
Trifunctional reaction active group polyhedral oligomeric silsesquioxane and preparation method thereof
CN116333315A
Easily-cut eleven-layer co-extruded high-barrier packaging film and preparation method thereof
CN118789912A
Water-shedding packaging material
JP2013018533A
Method for preparing a silica suspension in a potentially crosslinkable silicone material
WO2004063266A1
Cited By
Liquid food packaging cover film and preparation process
CN120348014A